The stratification of education systems and social background inequality of educational opportunity. (April 2022) - Traini, Claudia
This article aims to identify the moderating effect of two dimensions of the stratification of education systems (the extent to which the first selection is based on students' ability and the age of first selection) on social background gradient in educational attainment. Individual-level data of the European Social Survey (round 1 to 9) is complemented with new contextual indicators measuring various education systems' characteristics. This article's contribution to the debate is twofold. First, it simultaneously investigates two dimensions of the stratification of education systems that have never been analyzed in cross-country studies investigating long-term educational outcomes. Second, it provides a series of indicators of education systems' characteristics collected by means of an online expert survey whose validity and reliability is also tested. Findings show that the two dimensions of the stratification of education systems have opposite effects. As the first selection is increasingly based on students' ability, social background gradient in educational attainment increases. In contrast, postponing the age of first selection decreases social inequality in educational opportunity.